Approach to clinical laser application in pediatric dentistry: Pendekatan aplikasi laser secara klinis dalam kedokteran gigi anak - Jeffrey; Vinna K. Sugiaman (Makassar Dental Journal PDGI Makassar, 2022)
The modern concept of pediatric dentistry today is based on minimally invasive dentistry. Light amplification by the stimulated emission of radiation or Laser is one of the newest technologies available and is used for dental and oral care. This technology causes patient compliance with treatment to be maximized because the discomfort caused is very minimal. Lasers are an exci-ting technology and make pediatric dental care more optimal without causing many of the fear factors found in conventional dental care. This protocol has been developed long ago so that laser treatment can continue to evolve and is a safe and effective part of treatment. Although it has some disadvantages regarding cost and training, its use in pediatric dental procedures is well received by patients and their parents. Because of this, the use of lasers, especially in pediatric dentistry, is increasingly import-ant and needs to be developed. The American Academy of Pediatric Dentistry (AAPD) states that the use of laser as an alterna-tive method in the treatment of hard and soft tissues in the oral cavity for infants, children, adolescents, and patients with special health care needs, but dentists need additional training to apply it to pediatric dental care.